Students' perception of the SCAMPER technique on creative writing skill: A case study of an ESP class - Vigo Dewangga; Rizqi Febrian Pramudita; Enik Rukiati; Gullit Tornado Taufan; Nila Susanti; Suyik Binarkaheni (Politeknik Negeri Jember, 2026)
Creativity plays a crucial role in innovation, problem-solving, and both individual and societal advancement, enabling individuals to generate novel ideas, develop effective solutions, and approach challenges with adaptability. The SCAMPER technique is used to foster creative and innovative thinking, providing a structured method for idea generation and refinement. SCAMPER encompasses seven creative strategies: Substitute, Combine, Adapt, Modify, Put to Another Use, Eliminate, and Reverse. This study examines students' perceptions of SCAMPER in developing creative writing skills within English for Specific Purposes (ESP) classes. A qualitative case study method was employed, involving second-semester students from the Informatics Engineering Study Program enrolled in Intermediate English courses. Data collection methods included semi-structured interviews and questionnaires, providing insights into students’ experiences with SCAMPER in writing procedural texts. The findings reveal that the SCAMPER technique enhances creativity, cognitive flexibility, and innovation in writing, enabling students to produce varied and explorative texts. Furthermore, the approach supports critical thinking and deeper idea exploration. Although some students struggled with adapting to the creative thinking process, the overall response to SCAMPER was positive, highlighting its potential as an effective tool in ESP learning environments.